Impaired Cognitive Functioning in Cochlear Implant Recipients Over the Age of 55 Years: A Cross-Sectional Study Using the Repeatable Battery for the Assessment of Neuropsychological Status for Hearing-Impaired Individuals (RBANS-H) - Claes, Annes J.; Van de Heyning, Paul; Gilles, Annick; Hofkens-Van den Brandt, Anouk; Van Rompaey, Vincent; Mertens, Griet (Frontiers in Neuroscience, 2018)
Primary objective: To compare cognitive functioning among experienced, unilateral cochlear implant (CI) recipients and normal-hearing (NH) controls by means of the Repeatable Battery for the Assessment of Neuropsychological Status for Hearing-impaired individuals (RBANS-H). Methods: Sixty-one postlingually and bilaterally severely hearing-impaired CI recipients (median age: 71.0, range: 58.3 to 93.9 years) with at least one year of CI experience (median: 12.4, range: 1.1 to 18.6 years) and 81 NH control participants (median age: 69.9, range: 50.1 to 87.1 years) took part in this cross-sectional study. The RBANS-H was performed, as well as an audiometric assessment, including best-aided speech audiometry in quiet (monosyllabic words) and in noise (Leuven Intelligibility Sentences test). Results: The RBANS-H performances of the CI recipients (mean: 88.1 (14.9)) were significantly poorer than the those of the NH participants (mean: 100.5 (±13.2)), with correction of age, sex and education differences (general linear model: p= 0.001). The mean difference, corrected for the effects of these three demographic factors, was 8.8 (±2.5) points. Additionally, in both groups, a significant correlation was established between overall cognition and speech perception, both in quiet and in noise, independently of age. Conclusion: Experienced, unilateral CI recipients present subnormal cognitive functioning, beyond the effect of age, sex and education. This has implications for auditory rehabilitation after cochlear implantation and may highlight the need for additional cognitive rehabilitation in the long term after implantation. Long-term prospective and longitudinal investigations are imperative to improve our understanding of cognitive aging in severely hearing-impaired individuals receiving CIs and its association with CI outcomes.